1989
DOI: 10.1159/000181284
|View full text |Cite
|
Sign up to set email alerts
|

Total Deficiency of Growth Hormone and Prolactin, and Partial Deficiency of Thyroid Stimulating Hormone in Two Dutch Families: a New Variant of Hereditary Pituitary Deficiency

Abstract: Four out of 10 children in two unrelated families presented with a total pituitary growth hormone (GH) and prolactin deficiency and a partial thyrotropin (TSH) deficiency. The GH gene was intact in family I. The pituitaries, visualized by magnetic resonance imaging, were normal. All children responded well to GH and L-thyroxine therapy. Baseline plasma somatostatin and its peak response to arginine infusion were elevated in family I and they had a milder TSH deficiency than family II. Plasma insulin showed a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It has been suggested that the persistence of normal immune function in hypopituitary patients is due to the fact that most do not have absolute GH defi ciency [7], However, even in patients with a total GH, prolactin and TSH deficiency, due to a mutation in the Pit-1 gene [61], no clinical phenomena of immune dys function could be demonstrated [62], Similarly, in pa tients with a deletion of the GH-N gene no symptoms of immune dysfunction have been reported, except for the frequent occurrence of anti-GH antibodies during GH therapy.…”
mentioning
confidence: 99%
“…It has been suggested that the persistence of normal immune function in hypopituitary patients is due to the fact that most do not have absolute GH defi ciency [7], However, even in patients with a total GH, prolactin and TSH deficiency, due to a mutation in the Pit-1 gene [61], no clinical phenomena of immune dys function could be demonstrated [62], Similarly, in pa tients with a deletion of the GH-N gene no symptoms of immune dysfunction have been reported, except for the frequent occurrence of anti-GH antibodies during GH therapy.…”
mentioning
confidence: 99%
“…Sec ond, a patient heterozygous for a G -» T substitution in codon 271 was reported. The mechanism of the dominant effect of this GGG (arginine) TGG (tryptophan) muta tion is not completely understood [44], The third and fourth Pit-1 mutations were found in two Dutch families in which affected individuals had postnatal growth failure with complete deficiencies of GH and PrL, while their T4 levels were low prior to or following GH replacement [45,46], The family having normal T4 levels prior to GH replacement were homozygous for a G -» C substitution in codon 158 changing GCA (alanine) -» CCA (proline). This mutations interferes with the formation of Pit-1 homodimers and dramatically reduces the altered Pit-l's ability to activate transcription.…”
Section: Panhypopituitary Dwarfismmentioning
confidence: 99%
“…In August 1992, Pfaffle et al [12] described the molecular defect responsible for GH, Prl and TSH deficiency in the two Dutch families originally described by Wit et al [13], Two children in the first family had mild central hypothyroidism and were homozygous for a mutation that changed codon 158 from an alanine to a proline. In the second family, the children had more severe central hypothyroidism.…”
Section: ]mentioning
confidence: 99%